Освіта на магістерських програмах НаУКМА: думки студентів магістеріуму - Хуткий, Дмитро Олександрович; Хуткий, Дмитрий Александрович; Khutkyi, Dmytro O. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Для реформування освіти на магістерському рівні важливо враховувати думки студентів. Тому автор ставить за мету виявити думки студентів магістеріуму останніх років навчання щодо освіти на МП НаУКМА. Дослідження ґрунтується на емпіричних даних трьох репрезентативних опитувань 2005–2007 рр. З’ясовано, що більшість студентів повністю або майже задоволені викладанням (73,6 %), навчанням (74,5 %), наукою (66,6 %) та освітою в цілому (75 %), але їхні погляди залежать від ціннісних орієнтацій і соціальних профілів. The reforms of graduate school require informed policies considering students’ opinions. Therefore the aim of the research is to identify opinions of graduate students about education at master programs of NaUKMA. The inquiry utilizes the empirical base of representative sociological surveys of graduate students during 2005–2007. It was found out that overall the graduate students are completely or rather satisfied with teaching (73,6 %), study (74,5 %), and research (66,6 %) at the graduate programs; moreover, their average satisfaction with education in general is comparable to average in Ukraine. There are marked differences between opinions of students, connected with their value orientations and socio-demographic characteristics, study and work patterns. In particular, 50,8 % of surveyed students appraise traditional values, 27,4 % – scholarly work, and 21,8 % – their job; female students study more intensely, NaUKMA graduates are more critical.
Education at Master Programs of NaUKMA: Opinions of Graduate Students
Keywords: освіта; викладання; навчання; наука; студенти; education; teaching; study; science; students